BARSAGE (Barbershop dan Sport Massage) sebagai Peluang Usaha Melalui Pelatihan dan Strategi Digital bagi Karang Taruna Desa Tapaluluo Kabupaten Gorontalo - Al Ilham; Ryan Hidayat Rafiola; Haerul Ikhsan (Universitas Negeri Gorontalo, 2026)
Youth unemployment in Tapaluluo Village, Gorontalo Regency remains high due to limited vocational skills and low interest in entrepreneurship, even though barbershop and sport massage businesses have promising potential. This community service program aims to enhance the skills and entrepreneurial readiness of Karang Taruna members through the BARSAGE training. The method includes strengthening entrepreneurial knowledge, practical service training, and assistance in the use of digital media. Evaluation was conducted through knowledge assessments, observation of practical performance, and participant satisfaction surveys. The results showed an increase in entrepreneurial knowledge from an average score of 57.4 to 83.6; 24 out of 29 participants (82.7%) achieved competency in service practice; and participant satisfaction reached 91%. The program contributed to creating new business opportunities and encouraging youth economic independence, with sustainability potential through continued mentoring and the establishment of a Karang Taruna-based business unit.